Resuscitation of Newborn Piglets. Short-Term Influence of FiO(2) on Matrix Metalloproteinases, Caspase-3 and BDNF - Solberg, Rønnaug (Public Library of Science, 2010)
BACKGROUND: Perinatal hypoxia-ischemia is a major cause of mortality and cerebral morbidity, and using oxygen during newborn resuscitation may further harm the brain. The aim was to examine how supplementary oxygen used for newborn resuscitation would influence early brain tissue injury, cell death and repair processes and the regulation of genes related to apoptosis, neurodegeneration and neuroprotection. METHODS AND FINDINGS: Anesthetized newborn piglets were subjected to global hypoxia and then randomly assigned to resuscitation with 21%, 40% or 100% O(2) for 30 min and followed for 9 h. An additional group received 100% O(2) for 30 min without preceding hypoxia. The left hemisphere was used for histopathology and immunohistochemistry and the right hemisphere was used for in situ zymography in the corpus striatum; gene expression and the activity of various relevant biofactors were measured in the frontal cortex. There was an increase in the net matrix metalloproteinase gelatinolytic activity in the corpus striatum from piglets resuscitated with 100% oxygen vs. 21%. Hematoxylin-eosin (HE) staining revealed no significant changes. Nine hours after oxygen-assisted resuscitation, caspase-3 expression and activity was increased by 30–40% in the 100% O(2) group (n = 9/10) vs. the 21% O(2) group (n = 10; p<0.04), whereas brain-derived neurotrophic factor (BDNF) activity was decreased by 65% p<0.03. CONCLUSIONS: The use of 100% oxygen for resuscitation resulted in increased potentially harmful proteolytic activities and attenuated BDNF activity when compared with 21%. Although there were no significant changes in short term cell loss, hyperoxia seems to cause an early imbalance between neuroprotective and neurotoxic mechanisms that might compromise the final pathological outcome.